IDENTIFICATION OF RUBBER SEED OIL CONTENT (Havea Brasiliensis) - Karma, Taufiq; Hidayatullah, Mhd.; Fitri, Melsi Efrika (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
Rubber (Havea brasiliensis) is one of the many plantation communities in Indonesia, especially in South Kalimantan. Most rubber plant farming communities only use rubber sap as their source of income, even though there are still other than rubber sap that can be used, namely rubber seeds that contain around 40%-50% vegetable oil. The high oil content in rubber seeds can be used as cooking oil. The purpose of this study is to analyze how rubber seed oil processing works simply. This research method is the processing of rubber seed oil by adopting a simple method of making coconut oil, namely from the start of collecting rubber seeds, splitting rubber seeds from rubber seed meat, roasting, drying and drying, crushing and grinding, boiling / heating, oil separation, oil heating for oil purification, Oil output from rubber seeds.